The applicability of disabled access and facilities at bus terminals in Klang Valley / Nur Hasliana Hassan - Hassan, Nur Hasliana (Faculty of Architecture, Planning and Surveying, 2015)
Applicability of disabled access and facilities is crucial to serve disabled people at best. The applicability of these facilities refers to how useful they are in providing their service in situation when the users are disabled people. The applicability of disabled access and facilities means the usefulness of disabled access and facilities to offer their functions to disabled users. The first objective of the research is to understand the design requirements of disabled access and facilities in according to Malaysian Standard (MS). There are two MS to be referred i.e Malaysian Standard Code of Practice on Access for Disabled Persons to Public Buildings MS 1184 : 2002 and Malaysian Standard Code of Practice for Access of Disabled Persons Outside Buildings MS 1331 : 2003. The second objective of the research is to compare and analyse the difference among the disabled facilities in the bus terminals within Klang Valley areas. A checklist was used to collect data whether the facilities provided complied with both MS or not. The third objective of the research is to identify the applicability of the facilities provisions for persons with disabilities in bus terminals. In order to gain this data, interviews were conducted with the users. The respondent of the interviews is focused on disabled people including wheelchair user, ambulant people, visually impaired person or hearing impaired person. The results show the difference between the case studies regarding the disabled facilities and the users. The conclusion then drawn the applicability of disabled facilities provision. The major finding of the research is vast majority of the disabled facilities provided in bus terminals are complied with most design requirements as stipulated in both Malaysian Standards. However, to highlight the terminal with best applicability, Terminal Bersepadu Selatan is the best out of four bus terminals. Some of recommendations is the guiding blocks are vital in order to guide them to correct route as well as to warn if any hazard in front of them especially in public building and public transportation system. Plus, the facilities that already provided should be kept under supervision so that they are always in good condition.